COVID‐19 Pandemic and Cancer: The Importance of Early Palliative Care. (16th November 2020) - Potenza, Leonardo; Luppi, Mario; Efficace, Fabio; Bruera, Eduardo; Bandieri, Elena
Abstract : In terms of clinical and ethical situations, this narrative compares the COVID‐19 pandemic to the cancer endemic and shares information that may be helpful to improve the management of both future pandemics and cancer care.